PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI DI DENPASAR - Permana, I Made Bayu; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 9 No 1 (2020)DO - 10.24843/EJMUNUD.2020.v09.i01.p17, 2020)
The era of globalization is one of the driving factors for a change in an organization. The purpose of the study was to analyze the effect of transformational leadership on job satisfaction, analyze the influence of transformational leadership and job satisfaction on OCB and the role of job satisfaction in mediating the effect of transformational leadership on OCB employees of PBF PT Banyumas. Samples were determined as many as 39 people with saturated sampling techniques. Data collection is done by distributing questionnaires directly to PBF employees. PT. Banyumas and analyzed using calculative descriptive statistics and descriptive statistics in the form of classic assumption tests and path analysis. The results of data analysis show that transformational leadership variables have a positive effect on job satisfaction, job satisfaction and transformational leadership variables have a positive effect on OCB, job satisfaction variables have a positive and significant effect in mediating partially the effect of transformational leadership on OCB at PT Banyumas PBF. Keyword : Transformational leadership, job satisfaction, ocb.